Validation of Aceh Cultural Character-Building Instrument for Senior High School Students - Dina Rizki Fadilla; Mudjiran Mudjiran (International Journal of Applied Counseling and Social Sciences, 2020)
Aceh is one of the regions in Indonesia.Aceh is known as "Seurambi Meukkah," which has a diverse character and identity, starting from the language, the proverbs, and the cultures passed for generations.Aceh cultural character education is close to Islamic Sharia, which has applied for a long time.However, in reality, in the school environment, violence still exists in schools; for instance, being pinched, beaten, cursed, and bullying. The subjects in this study were high school students in Aceh who were randomly randomized and selected students who were true were native Acehnese. In this study, researchers needed 35 students. The results of this study indicated that out of 50 items, 39 items were valid, 11 items have been dropped, that the coefficient ? is at the significance level, 05>, 282 and a Cronbach alpha coefficient value of 0.932 was obtained. Based on the benchmark in interpreting the degree by using the degree of reliability, the alpha Cronbach value was 0.814, so that the Aceh cultural character education inventory could be said reliable.